The Implementation of Teacher Training Programs to Enhance Pedagogical Competence in Elementary Schools - Wicaksono, Bagus Koko; Harris, Taufiq; Suyitno, Suyitno (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Teachers' pedagogical competence is a key determinant of learning quality. However, preliminary observations at two elementary schools in Tosari indicated that teachers' pedagogical competence still needs improvement, as seen from the dominance of lecture methods, difficulties in designing innovative lesson plans, and limited integration of ICT. This study aims to analyze the implementation of teacher training programs in an effort to improve this pedagogical competence. The research uses a descriptive phenomenological qualitative approach, located at UPT SDN Podokoyo I Tosari. Data were collected through in-depth interviews, observation, and document studies, then analyzed using the interactive model of Miles, Huberman, and Saldana and verified through triangulation. The findings show that program implementation refers to Edward III's framework, where factors of communication, resources, disposition, and bureaucratic structure significantly influence. Needs-based and participatory training programs proved effective in improving teacher competence, especially in lesson planning, varied teaching methods, and the use of simple media. However, the sustainability of training impact requires systemic support such as ongoing mentoring and supportive school policies. This study concludes that well-planned and contextual training program implementation can be an effective strategy for teacher professional development at the elementary school level.